Delving within: the new science of the unconscious. Issue 1 (20th June 2017) - Paulson, Steve; Berlin, Heather A.; Ginot, Efrat; Makari, George
Abstract: What exactly is the relationship between conscious awareness and the unconscious mind? How, for example, does the brain classify and sort its different functions into conscious or unconscious processes? How has the history of human conceptualizations about the unconscious influenced current theories? Steve Paulson, executive producer of To the Best of Our Knowledge, moderated a discussion among neuroscientist Heather Berlin, psychologist Efrat Ginot, and psychiatrist George Makari to shed light on the history of the mind and the latest insights into the still emerging science of the unconscious.